Introduksi Teknologi Tepat Guna pada Industri Rumah Tangga (IRT) “Rambak Eco” Surakarta untuk Meningkatkan Efisiensi Proses Produksi dan Kualitas Produk - Setyaningrum Ariviani; Lia Umi Khasanah; Dwi Ishartani; Siswanti Siswanti; Windi Atmaka; Gusti Fauza; Dimas Rahadian Aji Muhammad; Muhammad Zulfan Hawari (PRIMA: Journal of Community Empowering and Services, 2025)
Introduction of Appropriate Technology at Home Industry (HI) “Rambak Eco” Surakarta to Increase the Production Process Efficiency and Product Quality. The home industry (HI) "Rambak Eco" produces unfried and fried crackers. IRT "Rambak Eco" has limited production capacity, reaching 10 kg of flour per day, so it has been unable to meet market demand. This limited production capacity is caused by the low efficiency of the production process, especially the cracker-slicing process, which still uses manual equipment consisting of knives and cutting boards. Apart from that, the IRT "Rambak Eco" also experienced problems related to inconsistent product quality. The inconsistent quality of cracker products is caused by the low understanding of Good Manufacturing Practices (GMP) for the Home Industry, manual packaging using PE plastic bags without labelling, and the manual slicing process impact on the thickness of the products was not uniform. Efforts to resolve the "Rambak Eco" home industry problems were carried out through community service activities, including introducing a semi-automatic cracker slicer, GMP training, and packaging and labelling. Based on the evaluation, the community service activities increased the efficiency of the “rambak” cracker production process and improved product quality at the "Rambak Eco" HI. The process efficiency was demonstrated by reducing the cracker's slicing process from 30 minutes/Kg to 10 minutes/Kg and the drying process from 9 to 4 hours. Improving product quality includes uniform shape and size of crackers and unfried and fried cracker products packaged in attractive packaging with informative labels.